Oral Health Impact Profile, EuroQol, and Assessment of Quality of Life instruments as quality of life and health-utility measures of oral health - Brennan, David S. (European journal of oral sciences, 2013)
Oral‐specific measures are often preferred to examine outcomes of oral disorders. However, generic measures can add additional information, including health utility. The aim was to assess the Oral Health Impact Profile (OHIP), EuroQol (EQ‐5D), and Assessment of Quality of Life (AQoL) instruments in relation to oral health in terms of their discriminative and convergent validities. Data were collected from adults, 30–61 yr of age, in Australia by mailed survey during 2009 and 2010, including the OHIP‐14, the EQ‐5D, and the AQoL, a range of self‐reported oral health variables, and by self‐rated oral and general health. Responses were collected from 1093 subjects (a response rate of 39.1%). The OHIP, the EQ‐5D, and the AQoL were associated with oral health variables, with effect sizes ranging from 0.6 to 1.1 for the OHIP, from 0.3 to 0.5 for the EQ‐5D, and from 0.4 to 0.6 for the AQoL. The OHIP tended to be more strongly correlated with self‐rated oral health (rho = −0.5) than with general health (rho = −0.3), whilst the EQ‐5D and the AQoL were less strongly correlated with oral health (rho = −0.3 and −0.3, respectively) than with general health (rho = −0.4 and −0.5, respectively). Whilst the OHIP was more sensitive to differences in oral health, the generic measures of EQ‐5D and AQoL both exhibited discriminative validity and convergent validity in relation to oral health variables, supporting their use in oral health studies.